The Role Of Laboratory Surveillance Systems In Early Detection And Prevention Of Outbreaks (Journal of Namibian Studies : History Politics Culture, 2022)
The occurrence of worldwide pandemics has escalated in frequency during the last ten years as a result of inadequate operation of surveillance systems that manage data on human health. An examination was undertaken of alternative infectious disease Early Warning Systems (EWSs) through the lens of surveillance data collection methods and their applicability in various contexts, as part of a systematic review. 68 publications were selected for inclusion in the final sample out of 1669. Chief complaints extracted from emergency department data are effective EWSs, but require standardized formats across institutions, according to the study. EWSs based on centralized public health records facilitate the exchange of information but are dependent on clinicians' case reporting. Web-based EWSs provide several benefits, including expedited alarm transmission and simplified reporting. Laboratory results and pharmaceutical sales did not establish solo effectiveness. The integration of surveillance data from staff and health records into the EWS design yielded positive results, with the most effective augmentation strategy being the daily notification of surveillance data during mass gatherings. Enhancing and refining pre-existing systems held greater significance in Low Middle Income Countries compared to the implementation of novel syndromic surveillance approaches. The research assessed the efficacy of EWSs across various resource settings and contexts.